Work & family : research informing policy - Parcel, Toby L.; Cornfield, Daniel B. (Thousand Oaks, Calif : Sage Publications, 2000)
Editors Toby Parcel and Daniel Cornfield draw on two major themes for this volume. First, that essential to an understanding of the interplay between work and family is an acknowledgment of the varied ways time influences work and family processes and outcomes. The editors and contributors look at time in both the macro historical sense as well as through examination of the more quotidian choices involved in balancing work and family. Second, the editors consider the social policy implications that inhere in these essays. Contributors to Work and Family have been encouraged to think explicitly about how governmental policies, as well as those of individual firms, can be derived from their research." "This collection is suited to courses on work and occupations, family studies, organizations, and gender roles, and will be of interest to scholars in these areas."--Jacket.
Includes bibliographical references and index.
Keywords: Work and family; Women -- Employment; Work and family -- United States; Women -- Employment -- United States